Morphology-Pragmatics Interface The Case of the Tanzanian Commercials in Swahili Newspapers - Lusekelo, Amani (AAeO - Afrikanistik-Aegyptologie-Online, 2010)
This work articulates the relationship between the choice of the vocabularies, their morphophonological modifications and the anticipated meanings in the language of commercial advertisements in Tanzanian Swahili newspapers. An eclectic approach that makes use of the Textual Analysis Approach and Lexical Morphology Theory brings into light important facts. For instance, apart from the use of standard Swahili, there is a good deal of English loan words which either undergo Swahilization morphologically or keep the original forms. Also, the intended meanings are captured by the intended audiences by, among others, the age and level of education of the newspapers’ readers. The contribution herein is that there is a link between the designed morphology of the words and the interpretation captured, at least in the language of commercials.